Airway Management in Pierre Robin Sequence: The Vancouver Classification. Issue 1 (February 2017) - Li, Wai-Yee; Poon, Alana; Courtemanche, Douglas; Verchere, Cynthia; Robertson, Sandra; Bucevska, Marija; Malic, Claudia; Arneja, Jugpal S.
Background: Pierre Robin sequence (PRS) is a triad of micrognathia, glossoptosis, and respiratory distress. There is no standard clinical classification used in the management of neonatal airway in patients with PRS. The goal of our study was to review the presentation and management of patients with PRS and formulate a clinical grading system and treatment algorithm. Methods: A 10-year retrospective review of all neonates diagnosed with PRS was performed after obtaining institutional ethics approval. Patients were identified using our cleft lip and palate program database. Inclusion criteria were 2 of the following 3 clinical features—glossoptosis, retrognathia, or airway obstruction. We collected demographic data, clinical information (coexisting airway morbidity, maxillary-mandibular discrepancy, type of intervention used, complications, and outcomes (feeding, length of stay, and airway status) during the first year of life. Results: Sixty-three patients met our inclusion criteria. Of these, 55 (87%) had cleft palate and 17 (27%) were syndromic. Forty-eight (76%) patients were managed by prone positioning. Of the 15 surgically managed patients, the initial procedure was floor of mouth release in 7, mandibular distraction osteogenesis (MDO) in 4, and tongue-lip adhesion in 4. Five patients with coexisting airway morbidity needed a second surgery; 2 had MDO and 3 tracheostomies (one patient was later decannulated). Seven (47%) of the surgically managed patients required a gastrostomy tube. Conclusion: At present, there is no consensus on neonatal airway management in infants with PRS. From our review of 63 patients with PRS, we hereby propose a simple 4-point classification system and treatment algorithm, based on clinical features.